1970
DOI: 10.13057/biodiv/d170128
|View full text |Cite
|
Sign up to set email alerts
|

Flowering, fruiting, seed germination and seedling growth of Macaranga gigantea

Abstract: The stages of flower and fruit development of Macaranga gigantea, its seed germination behavior in nature and from fruit harvesting, as well as the process of raising its seedlings in the laboratory were studied to determine the potential for production of M. gigantea seedlings. Five reproductive trees of M. gigantea were chosen as sources of seed. To estimate natural germination rates, four sample plots of 1 x 1 m 2 in four cardinal directions below the crown of every tree were set up. In addition, dry and we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 18 publications
0
10
0
2
Order By: Relevance
“…Dense vessels lower the risk of detrimental damage during stressful environmental conditions by enabling alternative pathways for water conductivity when cavitation occurs (Schmitz et al 2006). Vatica dulitensis is a slow-growing shade-tolerant species (Still 1993), and its vessel traits are unlikely to need a high hydraulic efficiency to support rapid transpiration. Instead they would ensure high hydraulic safety during occasional droughts when soil moisture is limiting.…”
Section: Discussionmentioning
confidence: 99%
“…Dense vessels lower the risk of detrimental damage during stressful environmental conditions by enabling alternative pathways for water conductivity when cavitation occurs (Schmitz et al 2006). Vatica dulitensis is a slow-growing shade-tolerant species (Still 1993), and its vessel traits are unlikely to need a high hydraulic efficiency to support rapid transpiration. Instead they would ensure high hydraulic safety during occasional droughts when soil moisture is limiting.…”
Section: Discussionmentioning
confidence: 99%
“…gigantea seedlings were collected from wildlings (wild seedlings) grew under host tree at Botanical Garden of Mulawarman University, Samarinda. Wildlings with similar size were collected and placed on wet newspapers, carried to nursery and transferred into polybags (Susanto et al 2016a). These seedlings were covered for one month to maintain its moisture.…”
Section: Seedling Preparationmentioning
confidence: 99%
“…The plant reproduces by forming flower buds initiated in the dry season and the fruits ripened in the rainy season. The seeds that fell under the tree germinated in approximately 24 days (Susanto et al 2016a). Bentos et al (2008) also reported that the flowering of pioneer trees happening at the end of the dry season and fruiting happening at the beginning of the wet season.…”
Section: Introductionmentioning
confidence: 95%
“…Mindawati et al (2010) also reported that soaking the seeds into 0.2% potassium nitrate solution for 20 minutes before germinate on sand medium able increasing seed germination rates up to 20%. On the other hand, Susanto et al 2016a reported that wet extraction without fruit drying treatment, able increased seeds germination (65%), with germination time first seeds (GTFS) 7.67 ± 1.15 days, germination time last seeds (GTLS) 17.33 ± 4.04, and mean germination times (MGT) 11.97 ± 1.93 days. In the germination process of M. gigantea seedlings showed that the highest relative growth rate obtained by seedlings planted on mushroom spawn waste media, followed by compost media, top soil media, and sand media.…”
Section: Introductionmentioning
confidence: 98%